Elevated fecal M2‐pyruvate kinase in children with cystic fibrosis: A clue to the increased risk of intestinal malignancy in adulthood?. Issue 5 (May 2015) - Pang, Tamara; Leach, Steven T; Katz, Tamarah; Jaffe, Adam; Day, Andrew S; Ooi, Chee Y
Abstract Background and Aim Adult patients with cystic fibrosis (CF) have an increased risk of gastrointestinal malignancies. We hypothesized that increased intestinal cell turnover beginning in childhood may explain the increased risk of malignancy in early adulthood. Therefore, we aimed to measure fecal M2‐pyruvate kinase (M2‐PK), a biomarker of intestinal cell turnover, in children with CF. To assess whether the increased cell turnover is secondary to intestinal inflammation, the secondary aims were to measure fecal calprotectin and evaluate its association with fecal M2‐PK. Methods Fecal samples, for M2‐PK and calprotectin measurements, were prospectively collected from children with CF and healthy controls (HC). Results Thirty‐three children with CF (mean [standard deviation] 7.3 [3.8] years old; 29 pancreatic insufficient [PI]) were enrolled and compared with 33 age‐matched HC. Fecal M2‐PK in CF patients (median [interquartile range, IQR]: 4.7 [1.5–9.7]) was greater than HC (1.0 [1.0–1.0] U/mL; P < 0.0001), and higher in PI (median [IQR]: 5.1 [1.8–13.7]) than pancreatic sufficient patients (1.0 [1.0–1.0] U/mL; P = 0.002). Fecal calprotectin was significantly elevated in CF than HC (median [IQR] 61.3 [43.8–143.8] vs 19.5 [19.5–35.1] mg/kg; P < 0.0001). However, there was no correlation between fecal M2‐PK and fecal calprotectin levels among subjects with CF (r = 0.29; P = 0.1). Conclusion Increased intestinal cell turnover is present in children with PI CF. The lack of relationship between fecal M2‐PK and calprotectin suggests that contributing factor(s) other than inflammation may be present.